Societal economic burden and determinants of costs for atopic dermatitis. Issue 4 (23rd November 2022) - Ortsäter, Gustaf; De Geer, Anna; Rieem Dun, Alexander; Geale, Kirk; Lindberg, Ingrid; Thyssen, Jacob Pontoppidan; von Kobyletzki, Laura B.; Metsini, Alexandra; Henrohn, Dan; Neregård, Petra; Cha, Amy; Cappelleri, Joseph C.; et al.
Abstract: Background: Atopic dermatitis (AD) is a common inflammatory skin disease while the economic burden of AD by severity is not adequately understood. Objective: To estimate the societal economic burden and to identify cost determinants of AD. Methods: In this population‐based, controlled cohort study in Sweden, patients with AD were identified through diagnosis codes in primary or secondary care or by dispensed medications using administrative healthcare registers. A reference cohort without AD was randomly selected from the general population. Healthcare costs (primary/secondary care visits and dispensed medication) and indirect costs (care for sick children and long‐term sick leave for adults) were calculated annually. AD patients were stratified by age (paediatric [age < 12], adolescent [12 ≤ age < 18] or adult [age ≥ 18]), and severity (mild‐to‐moderate [M2M] or severe AD) and matched to the reference cohort. Results: Compared with controls, the annual mean per‐patient direct healthcare costs in the first year following diagnosis were €941 and €1259 higher in paediatric patients with M2M and severe AD, respectively. In the first year following diagnosis, the mean indirect cost for care of sick children was €69 and €78 higher per patient in M2M and severe AD, respectively. In adolescents with M2M and severe AD, direct healthcare costs were €816 and €1260 higher, respectively. In adults, healthcare costs were €1583 and €2963 higher in patients with M2M and severe AD, respectively and indirect costs were €148 and €263 higher compared with controls. Management of comorbid medical conditions was an important driver of incremental healthcare costs. Total incremental societal economic burden for AD was €351 and €96 million higher in patients with M2M and severe AD, respectively, compared to controls. Conclusion: AD is associated with a significant societal economic burden primarily driven by the cost burden of M2M AD due to the high prevalence of this population. Regardless of severity level, management of non‐AD comorbidities is a major driver of total costs. Plain‐Language Abstract: The economic cost of atopic dermatitis Atopic dermatitis (AD) is a common chronic skin disease characterized by dry and itchy skin that often turns into red swollen skin during flare‐ups. This disease often first appears during childhood but may start at any age. The itch associated with the disease may be severe, sometimes described as unbearable affecting both the patients and the families of the patients. In this study, we estimated both the costs of healthcare visits and treatments for patients with AD including care and treatment for other associated diseases. We also estimated the cost of work absence for parents of children with AD as well as cost of sick leave for adults with AD. All costs were compared to that for a reference cohort (i.e., control group of individuals without AD). We found that patients with AD had higher healthcare costs compared to individuals without AD. We also observed that a significant proportion of healthcare costs for patients with AD was due to the management of other diseases. Moreover, the overall cost of care for sick children and sick leave was also higher for patients with AD compared to individuals without AD. In conclusion, AD not only contributes to a significant burden for the patients but is also associated with a significant economic burden. The economic burden of AD is mainly driven by patients with mild and moderate AD given the higher prevalence of this patient population. The recognition of AD as a disease with a high economic cost to society highlights the importance of optimizing care for this patient group. Abstract : Societal economic burden and determinants of costs for atopic dermatitis Atopic dermatitis causes a significant burden on patients and their families Healthcare costs generally increase with more severe disease, but the total societal economic burden is primarily driven by the cost burden of patients with mild‐to‐moderate atopic dermatitis due to the high prevalence of this population Regardless of severity level, management of non‐AD comorbidities is a major driver of total costs.